A New Insight Into Seawater-Basalt Exchange Reactions Based on Combined δ18O—Δ′17O—87Sr/86Sr Values of Hydrothermal Fluids From the Axial Seamount Volcano, Pacific Ocean - Zakharov, D. O.; Tanaka, R.; Butterfield, D. A.; Nakamura, E. (Frontiers in Earth Science, 2021)
The δ18O values of submarine vent fluids are controlled by seawater-basalt exchange reactions, temperature of exchange, and to a lesser extent, by phase separation. These variations are translated into the δ18O values of submarine hydrothermal fluids between ca. 0 and +4 ‰, a range defined by pristine seawater and equilibrium with basalt. Triple oxygen isotope systematics of submarine fluids remains underexplored. Knowing how δ17O and δ18O change simultaneously during seawater-basalt reaction has a potential to improve i) our understanding of sub-seafloor processes and ii) the rock-based reconstructions of ancient seawater. In this paper, we introduce the first combined δ17O-δ18O-87Sr/86Sr dataset measured in fluids collected from several high-temperature smoker- and anhydrite-type vent sites at the Axial Seamount volcano in the eastern Pacific Ocean. This dataset is supplemented by measurements of major, trace element concentrations and pH indicating that the analyzed fluids have reacted extensively with basalt. The salinities of these fluids range between 30 and 110 % of seawater indicating that phase separation is an important process, potentially affecting their δ18O. The zero-Mg endmember δ18O values span from -0.9 to +0.8 ‰, accompanied by the Δ′17O0.528 values ranging from around 0 to -0.04 ‰. However, the trajectory at individual site varies. The endmember values of fluids from focused vents exhibit moderate isotope shifts in δ′18O up to +0.8 ‰, and the shifts in Δ′17O are small, about -0.01 ‰. The diffuse anhydrite-type vent sites produce fluids that are significantly more scattered in δ′18O – Δ′17O space and cannot be explained by simple isothermal seawater-basalt reactions. To explain the observed variations and to provide constraints on more evolved fluids we compute triple O isotope compositions of vent fluids using equilibrium calculations of seawater-basalt reaction, including a non-isothermal reaction that exemplifies complex alteration of oceanic crust. Using a Monte-Carlo simulation of the dual-porosity model, we show a range of possible simultaneous triple O and Sr isotope shifts experienced by seawater upon reaction with basalt. We show the possible variability of fluid values, and the causal effects that would normally be undetected with conventional δ18O measurements.